Influencia de la profundidad de la compactación en la productividad de hortalizas en un suelo ándico de la sabana de Bogotá - Amézquita Collazos, Edgar; Hernández R., E.; Moreno O, O.J. (International Center for Tropical Agriculture, 1996)
To evaluate the influence of the depth of a compacted layer in the yields of some vegetables, in an Andisol, (Tibaitata, Sabana de Bogota) experimental plots compacted to 5, 10, 15 and 30 cm were used. Each depth resembled the compactation caused by the constant use of rotovator, light harrow, heavy harrow and disk plough, tools that are commonly used by formers in tillage operations in "La Sabana de Bogota". To test the influence of depth of compaction a split plot design experiment was used in which the main plot was the depth of compaction and the subplots the type of vegetables (cabbage, silver beet and carrots). The depth of the compacted layer had a big influence in the yields of all the tested vegetables. Assuming that the 30 cm depth of compacted layer produced 100 percent, when it was 5 cm the relative yields decreased down to 38, 32 and 22 percent for the same crops respectively, showing the negative influence of oompaction, which affects soil water storage capacity and nutrient absorption by reducing the available soil volume for rooting.